Application of Sensory Integration Training in the Treatment of Children with Attention Deficit Hyperactivity Disorder (ADHD) - Hou Yongmei (Medical Research and Its Applications Vol. 7, 2024)
Attention Deficit and Hyperactive Disorder (ADHD) is a common chronic neurodevelopmental disorder in childhood, whose onset cause and mechanism are not yet clear. This article compiles and analyzes a total of 67 relevant pieces of literature from the past 20 years with the keywords "children", "attention deficit hyperactivity disorder", and "sensory integration training" through CNKI and Pubmed. The search results show that sensory integration training has a good effect on improving the neurobiochemistry, executive function, sensory integration ability, daily behavior, intelligence, and social adaptation ability of children with ADHD; the combination of sensory integration training and drug therapy has a better effect than sensory integration training or drug therapy alone, and sensory integration training can improve the effectiveness of other non-drug treatments. This article provides researchers with a theoretical basis for ADHD and suggestions for frontline teachers and parents to correctly understand and intervene in children with ADHD.